Pengaruh Persepsi Manfaat Dan Kemudahan Bertransaksi Terhadap Penggunaan Aplikasi Oren By Kopnuspos Di Kota Metro - Ratna sari Sari; Andiana Rosid; Tyas Aisyah Nor Zureza (Universitas Muhammadiyah Metro, 2025)
The era of digitalization is increasingly simultaneously penetrating all aspects of life. The impact that is increasingly being felt has also led some people to think that nowadays society cannot be separated from the influence of technology to date. The emergence of convenience from every aspect ranging from education, business, health, industry and various things makes everything today very easy This study aims to find out (1) Does the perception of benefits affect the use of the Oren By Kopnuspos application in Metro city? (2) Does the ease of transaction affect the use of the Oren By Kopnuspos application in Metro City? (3) Does the Perceived Benefit and Ease of Transactions Affect the Use of the Oren By Kopnuspos Application in Metro City? The survey method was chosen as the primary data source. The survey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. Data collection was carried out using a questionnaire instrument or questionnaire. In this study, the population in this study was a company, namely the UMKM Kopnuspos cooperative. The sampling technique used accidental sampling with a total sample of 100 people. Data collection techniques using a questionnaire with a Likert scale. The results showed that 1) there was a positive and significant influence between the perceived benefits of using the Oren By Kopnuspos application 2) there was a positive and significant effect between the ease of transactions on the use of the Oren By Kopnuspos application 3) there was a positive and significant effect between the perceived benefits and ease of transaction using the Oren By Kopnuspos application.